Effect of Mass Stool Examination and Mass Treatment For Decreasing Intestinal Helminth and Protozoan Infection Rates in Bolivian Children: A Cross-Sectional Study. - Takao Asai; Claudia Còrdova Vidal; Wilma Strauss; Toshikazu Ikoma; Kazuo Endoh; Masaharu Yamamoto (Public Library of Science (PLoS), 2016)
Bolivia is one of the countries with a high intestinal helminth and protozoan infection rate. Despite the high prevalence of the parasitic infection, nationwide preventive measures for Bolivian children have not yet been implemented. We evaluated the effect of mass stool examination and treatment as a strategy for decreasing the infection rate. This study was conducted between 2013 and 2015 in children aged 2-18 years. A total of 2,033 stool samples (575 in 2013, 815 in 2014 and 642 in 2015) were collected and examined using the formalin-ether medical sedimentation method. As an anthelminthic medicine, nitazoxanide was given to all infected children within 2 months post-examination, each year. The effect of mass stool examination and treatment was evaluated based on the changes in the overall or individual parasitic infection rates during the study period. The overall parasitic infection rate decreased significantly from 65.2% in 2013 to 43.0% in 2015; a 22.2 percentage point decrease (P<0.001). Protozoan infection accounted for a large portion of the parasitic infections, in the following rates: 62.4% in 2013, 49.3% in 2014, and 41.0% in 2015. The rate of the most common helminth infection, Hymenolepis nana, decreased significantly from 9.0% in 2013 to 6.4% in 2014 to 3.4% in 2015 (P<0.001). Prevalence of the most common pathogenic protozoan infection, Entamoeba histolytica, decreased significantly from 19.0% in 2013 to 3.0% in 2015 (P<0.001). Conversely, the rate of Giardia intestinalis increased significantly from 16.5% in 2013 to 21.2% in 2015 (P<0.01). Mass stool examination and treatment for intestinal helminth and protozoan infections was effective for decreasing the overall parasitic infection rate in the study population, excluding Giardia intestinalis. Further studies on the long-term effect of mass stool examination and treatment for decreasing all intestinal parasitic infection rates in Bolivian children are needed.